Changes in Immunization Program Managers' Perceptions of Programs' Functional Capabilities during and after Vaccine Shortages and pH1N1. (November 2014) - Moriarty, Leah F.; Omer, Saad B.; Seib, Katherine; Chamberlain, Allison; Wells, Katelyn; Whitney, Ellen; Berkelman, Ruth; Bednarczyk, Robert A.
Objectives: We surveyed U.S. immunization program managers (IPMs) as part of a project to improve public health preparedness against future emergencies by leveraging the immunization system. We examined immunization program policy and Immunization Information System (IIS) functionality changes as a result of the Haemophilus influenzae type B (Hib) vaccine shortage and pandemic influenza A(H1N1) (pH1N1). Evaluating changes in immunization program functionalities and policies following emergency response situations will assist in planning for future vaccine-related emergencies. Methods: We administered three consecutive surveys to IPMs from 64 state, city, and territorial jurisdictions in 2009, 2010, and 2012. We compared IPMs' responses across either two or three years (e.g., changes in response or consistent responses across years) using McNemar's test. Results: Immunization programs maintained increases in functionality related to communication systems with health-care providers during this period. Immunization programs often did not maintain changes to IIS functionalities made from 2009 to 2010 (e.g., identifying high-risk and priority populations, tracking adverse events, and mapping disease risk) in the post-pandemic period (2010–2012). About half of IPMs reporting additional IIS functionality in identifying high-risk populations from 2009 to 2010 reported no longer having this function in 2012. There was an 18% decline in respondents reporting geographic information systems risk-mapping capability in IIS from 2010 to 2012. Conclusions: Because of the Hib vaccine shortage and pH1N1, immunization program needs and efforts changed to address evolving situations. The lack of sustained increases in resources or system functions after the pandemic highlights the need for comprehensive, sustainable public health emergency preparedness systems and related resources.